2020
DOI: 10.1038/s41598-020-61287-6
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 is indispensable for the S-nitrosylation of Parkin, which maintains function of mitochondria

Abstract: The DJ-1 gene, a causative gene for familial Parkinson's disease (PD), has been reported to have various functions, including transcriptional regulation, antioxidant response, and chaperone and protease functions; however, the molecular mechanism associated with the pathogenesis of PD remains elusive. To further explore the molecular function of DJ-1 in the pathogenesis of PD, we compared protein expression profiles in brain tissues from wild-type and DJ-1-deficient mice. Two-dimensional difference gel electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
(52 reference statements)
1
23
1
Order By: Relevance
“…Crucially, through NF- κ B regulation, DJ-1 controls the expression of mitochondrial uncoupling proteins, UCP4 and UCP5, that decrease mitochondrial membrane potential, thereby suppressing ROS production; meanwhile, DJ-1 binds to Complex I via NDUFA4 to maintain its activity, and is thus crucial for mDAN survival [ 472 ]. As previously described, DJ-1 is also involved in the nitrosylation of Parkin1 [ 311 ], and DJ-1 itself can be oxidised. This is crucial for neuroprotection, and indeed, levels of oxidised DJ-1 are reduced in Parkinson's patients [ 307 , 473 ], and low levels of DJ-1 increase vulnerability to oxidative stress [ 474 ].…”
Section: Autophagy and Oxidative Stress In Parkinson'smentioning
confidence: 94%
See 1 more Smart Citation
“…Crucially, through NF- κ B regulation, DJ-1 controls the expression of mitochondrial uncoupling proteins, UCP4 and UCP5, that decrease mitochondrial membrane potential, thereby suppressing ROS production; meanwhile, DJ-1 binds to Complex I via NDUFA4 to maintain its activity, and is thus crucial for mDAN survival [ 472 ]. As previously described, DJ-1 is also involved in the nitrosylation of Parkin1 [ 311 ], and DJ-1 itself can be oxidised. This is crucial for neuroprotection, and indeed, levels of oxidised DJ-1 are reduced in Parkinson's patients [ 307 , 473 ], and low levels of DJ-1 increase vulnerability to oxidative stress [ 474 ].…”
Section: Autophagy and Oxidative Stress In Parkinson'smentioning
confidence: 94%
“…Conversely, in the presence of high levels of oxidative stress, DJ-1 is oxidised to the sulfonic form; this isoform is inactive and predisposed to aggregate formation, and indeed, this overoxidised isoform has been detected in brains from Parkinson's patients [ 309 , 310 ]. In addition, Ozawa et al highlighted the crucial role of DJ-1 in the nitrosylation of Parkin, and suggested that DJ-1 inactivation reduces mitophagy, leading to mitochondrial dysfunction and Parkinson's pathogenesis [ 311 ].…”
Section: Autophagy and Redoxtasis Crosstalkmentioning
confidence: 99%
“…Indeed, DJ-1 has been described to interact with complex I [ 26 , 27 ] and, more recently, with the β subunit of F 1 F O ATP synthase [ 28 ], modulating their functionality. Moreover, the protein has been found to take part in the process of mitochondrial quality control, playing a role in the Parkin/PINK1-mediated mitophagy [ [29] , [30] , [31] , [32] ], and in the regulation of the mitochondrial dynamics [ [33] , [34] , [35] , [36] ]. Noteworthy, the protein has also been suggested to modulate endoplasmic reticulum-mitochondria tethering, playing a role in the modulation of calcium transients [ 37 , 38 ].…”
Section: Dj-1: a Multifunctional Protein Against Cellular Stressmentioning
confidence: 99%
“…Ozawa and colleagues performed a 2D gel electrophoresis-based proteomic analysis of brain tissue from DJ-1 deficient mice and found a significant change in protein expression of pathways related to energy production including glycolysis, creatine pathway, mitochondrial TCA cycle, and ROS signaling pathway [94]. According to their analysis, spots of proteins such as PDH were decreased in DJ-1 KO compared to WT mice (Figure 1).…”
Section: Dj-1 and The Regulation Of Glycolysis And The Tca Cyclementioning
confidence: 99%